Implementation of modern medical management into the system of chronic and social diseases control in the Black Sea region of Ukraine - Talalayev, K. O.; Vastyanov, R. S. (Journal of Education, Health and Sport, 2019)
The era of global transformation brings significant changes in public views and opinions – issues of socially dangerous diseases, as well as problems of education in this area, lose their “taboo character” over time. The participation in these processes of specialists from Ukrainian high medical educational institutions that are responsible for training students in the medical management direction is particularly noteworthy. Theoretical understanding of modern management elements in health care as part of management science, the study of methods, forms, means of its practical introduction are attracting increasing attention of scientists who are developing, substantiating and expanding new possibilities of practical application of innovative management technologies in the field of health care and new directions for their application have been identified. This is also due to other modern technologies use for which traditional medical care stereotypes should be restored, a new outlook formed and the prevention process participants mentality changed. The system of modeled measures for social and chronic illnesses should be proactive and preventive resulting in changing citizens behaviour to be faithful and safe. The introduction of modern elements of medical management into the system of control over chronic and social diseases in the Black Sea region ofUkraineshould be built taking into account public health features, which include interdisciplinary approaches of epidemiology, biostatistics and health. One should outline the other important areas for this policy - environmental and public health, psycho-hygiene, traffic safety, health economics, public policy, mental health, insurance medicine, occupational safety and health.